Subjective Appropriation of Musical Form in Schumann’s Carnaval, Op. 9 - Pereira, Teresa da Palma (2019)
The aim of this article is to analyze musical form in german composer Robert Schumann’s works (8 June 1810 – 29 July 1856), particularly that of piano solo piece Carnaval, op. 9, trying to understand what is revealed by the way he uses it in relation to his personality, not only in artistic terms (taking into account the context of German Romanticism) but also on a deeper psychological level. To come to an understanding of Schumann’s use of form, this paper begins with a brief description of the evolution of musical form since Viennese Classicism, with additional references to the baroque system of ‘affects’. Form in Schumann is compared with that of other significant composers of the romantic period and various points of intersection between music and other arts are analyzed, especially literature, in certain key works of this period. Parting from these reflections, we explore the question of the expressive intention behind his handling of form in Carnaval, op. 9. The aim of the investigation of this aspect is to understand how far the innovatory use of this parameter in Schumann, reflects a unique vision of the art of music.